Measurement of the direct photon spectrum in Y(1S) decays - Nemati, B; Richichi, S; Ross, W; Skubic, P; Wood, M; Bishai, M; Fast, J; Gerndt, E; Hinson, J; Menon, N; Miller, D; Shibata, E; et al. (1997)
Using data taken with the CLEO II detector at the Cornell Electron Storage Ring, we have determined the ratio of branching fractions: Rγ≡Γ(Y(1S)→γgg)/Γ(Y(1S)→ggg)=[2. 75±0.04(stat)±0.15(syst)]%. From this ratio, we have determined the QCD scale parameter ΛMS(defined in the modified minimal subtraction scheme) to be ΛMS=233±11±59 MeV, from which we determine a value for the strong coupling constant αs(MY(1S))=0.163±0.002±0.014, or αs(MZ)=0.110±0.001±0.007.